Study of Provenance and Site Variability on Calorific Value and Other Fuel Properties of Teak Stem - Asri Prasaningtyas; Joko Sulistyo (Masyarakat Peneliti Kayu Indonesia, 2014)
Currently Perum Perhutani has conducted efforts to improve the productivity of teak forest by provenance trial. However, only a few studies have so far considered the variation of these main fuel properties of wood under the influence of external factors such as location and provenance. On the other side, the huge amount of waste was regularly generated from primary and secondary wood processings. Therefore, in this research, the calorific value and other fuel properties were investigated and related to provenance and growth site. This research used the stem wood and bark of five provenances (1 to 5) of teaks that were planted at three sites of Perhutani stand (Bojonegoro, Ngawi, Ciamis). The fuel characterisctics of bark were only evaluated at Ciamis site. Compared to bark, wood generally had lower values in ash content, volatile matter content, and density, but had higher values in fixed carbon content, calorific value, and Fuelwood Value Index levels. The caloric values of teak wood and bark were 4,191 4,520 cal/g and 3,545 3,939 cal/g, respectively. Provenance and site interaction had significant effect to the ash content, density, and calorific value in wood. The samples from Ciamis site (code Ft) had the highest level in calorific value. However, the relation between calorific value and density is not clear in this experiment. With regard to bark, provenance 3 (Ft) showed the best energy properties.